Lygdamus : Corpus Tibullianum III. 1-6: Lygdami elegiarum liber - Navarro Antolín, Fernando. (Mnemosyne, Supplements, 1995)
This volume is an in-depth study of the short poetic cycle of Lygdamus, one of the authors included in Book III of the Corpus Tibullianum . The Introduction analyzes the controversial quaestio Lygdamea (identity and dating of the poet), the relationship between Lygdamus and his beloved, Neaera, the incorporation of his poems into the Corpus Tibullianum , and the manuscript tradition. This is followed by a rigorous critical edition (taking fully into account the earliest editions and conjectures). Finally, there is a detailed and exhaustive line-by-line and word-by-word commentary on each poem, paying particular attention to elegiac terms and motifs. This is the first comprehensive study of the work of Lygdamus, considered as a poet with his own literary identity.